Soil fauna drives vertical redistribution of soil organic carbon in a long‐term irrigated dry pine forest - Claudia Guidi; Beat Frey; Ivano Brunner; Katrin Meusburger; Michael E. Vogel; Xiaomei Chen; Tobias Stucky; Dariusz J. Gwiazdowicz; Piotr Skubała; Arun K. Bose; Marcus Schaub; Andreas Rigling; et al. (Global Change Biology, 2022)
Summer droughts strongly affect soil organic carbon (SOC) cycling, but net effects on SOC storage are unclear as drought affects both C inputs and outputs from soils. Here, we explored the overlooked role of soil fauna on SOC storage in forests, hypothesizing that soil faunal activity is particularly drought‐sensitive, thereby reducing litter incorporation into the mineral soil and, eventually, long‐term SOC storage. In a drought‐prone pine forest (Switzerland), we performed a large‐scale irrigation experiment for 17 years and assessed its impact on vertical SOC distribution and composition. We also examined litter mass loss of dominant tree species using different mesh‐size litterbags and determined soil fauna abundance and community composition. The 17‐year‐long irrigation resulted in a C loss in the organic layers (−1.0 kg C m −2 ) and a comparable C gain in the mineral soil (+0.8 kg C m −2 ) and thus did not affect total SOC stocks. Irrigation increased the mass loss of Quercus pubescens and Viburnum lantana leaf litter, with greater effect sizes when meso‐ and macrofauna were included (+215%) than when excluded (+44%). The enhanced faunal‐mediated litter mass loss was paralleled by a many‐fold increase in the abundance of meso‐ and macrofauna during irrigation. Moreover, Acari and Collembola community composition shifted, with a higher presence of drought‐sensitive species in irrigated soils. In comparison, microbial SOC mineralization was less sensitive to soil moisture. Our results suggest that the vertical redistribution of SOC with irrigation was mainly driven by faunal‐mediated litter incorporation, together with increased root C inputs. Our study shows that soil fauna is highly sensitive to natural drought, which leads to a reduced C transfer from organic layers to the mineral soil. In the longer term, this potentially affects SOC storage and, therefore, soil fauna plays a key but so far largely overlooked role in shaping SOC responses to drought.